A synopsis of the Family Cordagalmatidae fam. nov. (Cnidaria, Siphonophora, Physonectae) - Pugh, P. R. (Zootaxa, 2016)
The genus Cordagalma is reviewed and a re-description given of one of the extant species, C. ordinatum (Haeckel). In addition, four new species are described in the genus Cordagalma, namely C. abyssorum sp. nov., C. bimaculatum sp. nov., C. isocarrei sp. nov. and C. rugosum sp. nov. All these species have similar larval-type tentilla. A fifth new species, which has extraordinary tentilla, with an involucrum forming two flaps, is placed in a new genus Cardianecta gen. nov. as C. parchelion sp. nov. The significant differences that all these species have from other physonects is considered to warrant the establishment of the family Cordagalmatidae fam. nov. for them. This family is diagnosed purely on the presence of heart-shaped nectophores budded on the ventral side of the nectosome.